PERANCANGAN MOTION GRAPHIC SEBAGAI MEDIA PROMOSI ALTERNATIF MUSEUM BAHARI JAKARTA - Felix Margery; Garry Saputra (Universitas Bunda Mulia, 2023)
The Jakarta Maritime Museum is a cultural heritage located at Jalan Pasar fish number one, Penjaringan sub-district, North Jakarta. This museum stores various collections of boats, traditional ships, preserved marine life, and there are still many marine collections in Indonesia. This museum was crowded with visitors until 2016, but when it entered 2017 to 2021 the Jakarta Maritime Museum experienced a quiet or decreased number of visitors. This is due to the Jakarta Maritime Museum's lack of promotion efforts. This study uses a descriptive qualitative research method and the result of this research is a motion graphic